"If your mother does not teach you, the world will...": a qualitative study of parent-adolescent communication on sexual and reproductive health issues in Border districts of eastern Uganda - Patricia Ndugga; Betty Kwagala; Stephen Ojiambo Wandera; Peter Kisaakye; Martin K. Mbonye; Fred Ngabirano (BMC, 2023)
Abstract Background Adolescents experience a host of sexual and reproductive health (SRH) challenges, with detrimental SRH and socio-economic consequences. These include early sexual debut, sexually transmitted infections including HIV/AIDS, teenage pregnancy, and early childbearing. Parent-adolescent communication about SRH has significant potential to reduce adolescents' risky sexual behaviors. However, communication between parents and adolescents is limited. This study explored the facilitators and barriers to parent-adolescent communication about sexual and reproductive health. Methods We conducted a qualitative study in the border districts of Busia and Tororo in Eastern Uganda. Data collection entailed 8 Focus Group Discussions comprising of parents, adolescents (10-17 years), and 25 key informants. Interviews were audio-recorded, transcribed, and translated into English. Thematic analysis was conducted with the aid of NVIVO 12 software. Results Participants acknowledged the key role parents play in communicating SRH matters; however, only a few parents engage in such discussions. Facilitators of parent-adolescent communication were: having a good parent-child relationship which makes parents approachable and motivates children to discuss issues openly, a closer bond between mothers and children which is partly attributed to gender roles and expectations eases communication, and having parents with high education making them more knowledgeable and confident when discussing SRH issues with children. However, the discussions are limited by cultural norms that treat parent-child conversations on SRH as a taboo, parents' lack of knowledge, and parents busy work schedules made them unavailable to address pertinent SRH issues. Conclusion Parents' ability to communicate with their children is hindered by cultural barriers, busy work schedules, and a lack of knowledge. Engaging all stakeholders including parents to deconstruct sociocultural norms around adolescent SRH, developing the capacity of parents to confidently initiate and convey accurate SRH information, initiation of SRH discussions at early ages, and integrating parent-adolescent communication into parenting interventions, are potential strategies to improve SRH communication between parents and adolescents in high-risk settings such as borders.